DE PROFESSOR A EMPRESÁRIO: CONTRIBUIÇOES DE ANTONIO VERONEZI AO ENSINO SUPERIOR - Santos, Maisa Alves dos (2014)
The history of the foundation and development of an educational institution, can not be detached from the events of the country, especially if within the last half century, unique period in history, in which higher education has expanded rapidly, especially the private sector. This study of the Brazilians university education, considering the history of the University Guarulhos, has the background of the life story of its founder and current Chancellor Antonio Veronezi, as a qualitative research method, constructed through auto-biographical interviews. Identifying the narratives defining moments in the history of Brazilian´s education, they were contextualized in the political aspect, economic and social. The changes of the industrialization process were also surveyed looking to present the development of the town of Guarulhos, generating demand for the university education since 1970s maintained to date. The educational path, entering the education sector, the development of management skills and the transformation of the high school teachers in one of the most important businessmen and representative of the sector, endow sense of the issues raised, which may be answered by researchers at history, pedagogy or management, including: democratization of the access to Higher Education Institutions, the quality of university education, the social representations of administrators and the commercialization process of the sector.